Current Issues and Advances in the Dairy Industry 2023
DOI: 10.5772/intechopen.111776
|View full text |Cite
|
Sign up to set email alerts
|

Lactic Acid Bacteria: Review on the Potential Delivery System as an Effective Probiotic

Abstract: Lactic acid bacteria are gram-positive microorganisms that are characterized by the production of lactic acid as a key fermentation product. LAB, specifically Lactobacillus delbrueckii subsp. bulgaricus, are essential dairy starter cultures for the manufacture of several fermented dairy products such as yogurt. Some LAB are useful microorganisms and are well known to have probiotic effects to provide foods with unique sensory qualities such as aroma and taste. Probiotic strains help to strengthen the human imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…(2000) found that adding Lacticaseibacillus rhamnosus (HN001, DR20), Lactobacillus acidophilus (HN017), Bifidobacterium lactis HN019 and B. lactis (HN019, DR10) strains to the diet improved various measures of both acquired immunity and natural immunity. Probiotics may influence the maturation of immune cells and their products not only in the gut but also in systemic immunological organs like the lymph node and spleen, resulting in tumour inhibition and these suggest that probiotics could be useful dietary supplements against neoplastic susceptibility due to their wide influence on the host's local and systemic immune mechanisms (Yu & Li, 2016; Yeboah et al ., 2023).…”
Section: Definition Of Probioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2000) found that adding Lacticaseibacillus rhamnosus (HN001, DR20), Lactobacillus acidophilus (HN017), Bifidobacterium lactis HN019 and B. lactis (HN019, DR10) strains to the diet improved various measures of both acquired immunity and natural immunity. Probiotics may influence the maturation of immune cells and their products not only in the gut but also in systemic immunological organs like the lymph node and spleen, resulting in tumour inhibition and these suggest that probiotics could be useful dietary supplements against neoplastic susceptibility due to their wide influence on the host's local and systemic immune mechanisms (Yu & Li, 2016; Yeboah et al ., 2023).…”
Section: Definition Of Probioticsmentioning
confidence: 99%
“…Throughout human life, the gastrointestinal tract (GIT) acts as a reservoir for a diverse range of microorganisms, predominantly bacteria, known as gut microbiota. These microorganisms have a significant impact on the host's health and well‐being through periods of homeostasis and illness (Yeboah et al ., 2023). Consuming probiotics can aid in preserving an individual's overall health and wellness, particularly in those who are already in good health.…”
Section: Definition Of Probioticsmentioning
confidence: 99%